CD19 Isoforms Enabling Resistance to CART-19 Immunotherapy Are Expressed in B-ALL Patients at Initial Diagnosis. Issue 5 (June 2017) - Fischer, Jeannette; Paret, Claudia; El Malki, Khalifa; Alt, Francesca; Wingerter, Arthur; Neu, Marie A.; Kron, Bettina; Russo, Alexandra; Lehmann, Nadine; Roth, Lea; Fehr, Eva-M.; Attig, Sebastian; et al.
Abstract : B-cell acute lymphoblastic leukemia (B-ALL) is the commonest childhood cancer and the prognosis of children with relapsed or therapy refractory disease remains a challenge. Treatment with chimeric antigen receptor-modified T cells targeting the CD19 antigen (CART-19 therapy) has been presented as a promising approach toward improving the outcome of relapsed or refractory disease. However, 10%–20% of the patients suffer another relapse. Epitope-loss under therapy pressure has been suggested as a mechanism of tumor cells to escape the recognition from CART-19 therapy. In this work, we analyzed the expression of CD19 isoforms in a cohort of 14 children with CD19 + B-ALL and 6 nonleukemia donors. We showed that an alternatively spliced CD19 mRNA isoform lacking exon 2, and therefore the CART-19 epitope, but not isoforms lacking the transmembrane and cytosolic domains are expressed in leukemic blasts at diagnosis in children and in the bone marrow of nonleukemia donors. Furthermore, we clarified the sequence of a further isoform lacking the epitope recognized by CART-19 therapy and disclosed the presence of new isoforms. In comparison with the children, we showed that alternatively spliced CD19 mRNA isoforms affecting exon 2 are also expressed in 6 adult patients with CD19 + B-ALL. On top of that, one of the adults expressed an isoform lacking the CD19 transmembrane and cytosolic domains. In conclusion, we proved that some of the CD19 isoforms contributing to CART-19 escape already preexist at diagnosis and could evolve as a dominant clone during CART-19 therapy suggesting the application of combined treatment approaches. Abstract : Supplemental Digital Content is available in the text.